Properties of wood-plastic composites made from alien invasive tree waste and recycled low-density polyethylene for interior use in social housing - Mohammed, Abubakar Sadiq (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.